The impact of use of traditional medicine on pregnancy outcomes in Chipinge District; Manicaland Province: Zimbabwe - Tinashe, Kureya; Miriam, Chitura; Auxillia, Professor Chideme Munodawafa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The prevalence of use of traditional medicine to prepare for child birth in Chipinge district is pronounced. No research has been done to examine the impact of use of traditional medicine on pregnancy outcomes in Chipinge district. It is from this background that this study was conducted to determine the impact of traditional medicine on pregnancy outcomes. An unmatched 1:1 case control study design was used to assess the pregnancy outcomes of 40 mothers who used traditional medicine and 40 mothers who did not. The mothers were between 20 and 35years of age, parity range of 1 to 4, identified from the delivery record of Mahenye and Mabee record book, period July 2015 and February 2016. The most commonly used traditional medicine was elephant dung. A young age (20-25years) and perceiving that traditional medicine is effective were associated with using traditional medicine. Low knowledge of traditional medicine and low knowledge of health risks of traditional medicine was protective of using the medicine. Precipitate labour was significantly associated with the use of traditional medicine for childbirth.